Exploring English as a Foreign Language Instructors’ Self-Derived English Language Policies at Higher Education Level: A Case Study in the Saudi Context - Alnasser, Suliman M. N. (Frontiers in Education, 2022)
Education in Saudi Arabia employs English as a foreign language. Several researchers have examined language policies governing English use. Current research suggests that official policies do not exist and self-English language policies (ELPs) are in place without any type of governance. Therefore, this study aims to investigate the nature of self-ELPs in Saudi Arabia and how the country can benefit from engendering institutional changes. An eight-item survey was conducted with an open-ended section and received responses from faculty members affiliated with English departments around the country (n = 213). Semi-structured interviews with eight chairpersons from different English departments were also organised. The findings reveal that the majority of faculty practice self-ELPs very frequently, in both official and non-official situations. It is concluded that English departments in the academia in Saudi Arabia are ready to enforce official ELPs and accept the idea of internationalising their academic services worldwide.